Understanding the micro and macro politics of health: Inequalities, intersectionality & institutions - A research agenda - Gkiouleka, Anna; Huijts, Tim; Beckfield, Jason; Bambra, Clare (Social science & medicine (1982), 2018)
This essay brings together intersectionality and institutional approaches to health inequalities, suggesting an integrative analytical framework that accounts for the complexity of the intertwined influence of both individual social positioning and institutional stratification on health. This essay therefore advances the emerging scholarship on the relevance of intersectionality to health inequalities research. We argue that intersectionality provides a strong analytical tool for an integrated understanding of health inequalities beyond the purely socioeconomic by addressing the multiple layers of privilege and disadvantage, including race, migration and ethnicity, gender and sexuality. We further demonstrate how integrating intersectionality with institutional approaches allows for the study of institutions as heterogeneous entities that impact on the production of social privilege and disadvantage beyond just socioeconomic (re)distribution. This leads to an understanding of the interaction of the macro and the micro facets of the politics of health. Finally, we set out a research agenda considering the interplay/intersections between individuals and institutions and involving a series of methodological implications for research - arguing that quantitative designs can incorporate an intersectional institutional approach. •Bridges intersectionality and institutional approaches to health inequalities.•Considers health inequalities beyond socioeconomic status.•Considers the intersections between institutions and individuals.•Emphasises the macro and the micro facets of the politics of health.•Suggests an intersectionality and institutionally informed research agenda.